2004
DOI: 10.1002/hed.20097
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of fluorine‐18 fluorodeoxyglucose positron emission tomography in patients with a residual structural abnormality after definitive treatment for squamous cell carcinoma of the head and neck

Abstract: Background. Residual structural abnormalities after definitive treatment of head and neck squamous cell carcinoma (HNSCC) are common and pose difficult management problems. The usefulness of fluorine-18 fluorodeoxyglucose positron emission tomography (FDG PET) to supplement conventional evaluation with clinical and standard radiologic examination (CE) in such patients was assessed.Methods. Fifty-three eligible patients were identified with residual structural abnormalities on CE. True disease extent could be v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 11 publications
1
35
0
2
Order By: Relevance
“…49,78). In addition, FDG-PET can define the extent of the primary disease before and after chemoradiotherapy; in contrast to estimates based on conventional imaging, the FDG-PETdefined extent of disease was a significant predictor of survival (P < 0.0001) in one recent study (79). FDG-PET is particularly accurate for staging local nodal spread, a key factor for prognosis and treatment planning.…”
Section: Fdg-pet Validated For Staging and Diagnosis: A Biomarker Of mentioning
confidence: 99%
See 1 more Smart Citation
“…49,78). In addition, FDG-PET can define the extent of the primary disease before and after chemoradiotherapy; in contrast to estimates based on conventional imaging, the FDG-PETdefined extent of disease was a significant predictor of survival (P < 0.0001) in one recent study (79). FDG-PET is particularly accurate for staging local nodal spread, a key factor for prognosis and treatment planning.…”
Section: Fdg-pet Validated For Staging and Diagnosis: A Biomarker Of mentioning
confidence: 99%
“…In detection of recurrent disease, FDG-PET has greater sensitivity and specificity than conventional imaging; CT is limited by the anatomic distortion commonly seen following treatment due to inflammation and edema and typically requires serial examinations. In 53 patients with residual structural abnormalities following definitive treatment, FDG-PET changed patient management in 40%; planned surgery was determined to be futile in 14 patients based on negative FDG-PET scan (79). Indeed, FDG-PET has a high negative predictive value (89% in one study of 75 patients; ref.…”
Section: Fdg-pet Validated For Staging and Diagnosis: A Biomarker Of mentioning
confidence: 99%
“…As the clinical role of PET has continued to evolve, there has been increasing evidence reporting a strong correlation with metabolic response and prognosis after chemoradiation in malignancy. Our institution has previously reported the powerful prognostic stratification achieved by 18 F-FDG PET metabolic response across a range of cancer types (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Several studies have suggested that 18 F-FDG PET might be useful for assessment of therapeutic responses (3)(4)(5)(6). However, 18 F-FDG is also metabolized at sites of inflammation and in other reactive states, so that false-positive results may be obtained because of inflammatory changes remaining within the first few posttreatment months.…”
mentioning
confidence: 99%